2022
DOI: 10.14710/jitaa.47.4.340-345
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect on semen quality of Limousine and Simmental bulls

Abstract: This study aimed to determine the effect of breed and season on the semen quality of AI bulls. The material used was n= 78,648 records of ejaculated semen from 85 Limousine and 88 Simmental bulls collected between period 2010 and 2020. Semen qualities evaluated in the study were: ejaculate vol-ume (Vol), pH, individual sperm motility (ISM), sperm concentration (SC), and post-thawing motility (PTM). The data was analyzed by using a MIXED model with breeds and seasons as fixed effects and animals as random effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Although the optimal point of sperm motility value has not been found in this study, several previous studies reported that the age factor had a significant effect on sperm motility (Boujenane & Boussaq, 2013;Sitanggang, 2018;Suyadi et al, 2020). The effect of seasons on FSM was consistent with previous studies on Simmental Bulls (Hapsari et al, 2022), Limousine Bulls (Konenda et al, 2020), Thapkar Bulls (Perumal et al, 2017), and Karan Fries Bulls (Bhakat et al, 2014). Other studies suggest a link between temperature and the continuity of spermatogenesis in terms of the effect of season on sperm motility (Konenda et al, 2020), where heat stress can reduce sperm motility (Selçuk et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Although the optimal point of sperm motility value has not been found in this study, several previous studies reported that the age factor had a significant effect on sperm motility (Boujenane & Boussaq, 2013;Sitanggang, 2018;Suyadi et al, 2020). The effect of seasons on FSM was consistent with previous studies on Simmental Bulls (Hapsari et al, 2022), Limousine Bulls (Konenda et al, 2020), Thapkar Bulls (Perumal et al, 2017), and Karan Fries Bulls (Bhakat et al, 2014). Other studies suggest a link between temperature and the continuity of spermatogenesis in terms of the effect of season on sperm motility (Konenda et al, 2020), where heat stress can reduce sperm motility (Selçuk et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The average sperm motility in this study was lower than that reported by Indriastuti et al [36], which was >80%. Sperm motility is influenced by various factors, such as age, individual male characteristics, season, and temperature [3,37,39,40]. Variations in male sperm motility are also influenced by changes in mitochondrial function in the production of adenosine triphosphate [36].…”
Section: Semen Quality In Bali Bulls With Either Normal or Poor Sperm...mentioning
confidence: 99%
“…Semen quality determines the success of artificial insemination (AI) [1,2]. AI is an early-stage biotechnological breakthrough that improves livestock's genetic quality, especially cattle [3]. Existing evidence indicates that the success rate of AI remains relatively low; bulls in Indonesia have fertility levels below 60% [4].…”
Section: Introductionmentioning
confidence: 99%